Rancang Bangun Alat Pemantau Kualitas Udara Sekitar Berbasis Mikrokontroler AVR ATMega 8 Dengan Penampil Dot Matrix - Emir Nasrullah; Yulliarto Raharjo (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2009)
Air pollution recently has attained an apprehension level, in line with the speed of vehicle production and industrial development. Air quality monitoring system that can display air condition, temperature and humidity is expected to be one solution in overcoming bad impact of air pollution problems. This research is aimed to produce an air quality and condition monitoring system device using gas sensor TGS-2600 and SHT11 for sensing temperature and humidity variables. Data from sensors are processed using AVR AT Mega 8 and Basic Stamp-2e microcontrollers, whereas information display using dot matrix circuit. The final result is a monitoring system device which can display air quality and condition data on its dot matrix display. Information displayed in form of running text: temperature in Celcius unit humidity in percent RH unit, and air quality refer to concentration level of one type of gas pollutant i.e. carbon monoxide concentration.